2016
DOI: 10.1038/srep37659
|View full text |Cite
|
Sign up to set email alerts
|

CCL5/RANTES contributes to hypothalamic insulin signaling for systemic insulin responsiveness through CCR5

Abstract: Many neurodegenerative diseases are accompanied by metabolic disorders. CCL5/RANTES, and its receptor CCR5 are known to contribute to neuronal function as well as to metabolic disorders such as type 2 diabetes mellitus, obesity, atherosclerosis and metabolic changes after HIV infection. Herein, we found that the lack of CCR5 or CCL5 in mice impaired regulation of energy metabolism in hypothalamus. Immunostaining and co-immunoprecipitation revealed the specific expression of CCR5, associated with insulin recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 69 publications
(85 reference statements)
0
45
0
1
Order By: Relevance
“…The beneficial effects of CCR5 deficiency were correlated with reduced recruitment and the M2dominant shift of macrophages in adipose tissues (Kitade et al, 2012). However, this finding is contrary to Chou et al' s studies, which suggested that the CCR5 gene knockout in mice impairs the regulation of energy metabolism in the hypothalamus (Chou et al, 2016). Both in vitro tissue culture and ex vivo stimulation studies indicated that the activation of PI3K-Akt pathways and insulin signaling were impaired in the hypothalamus of CCR5 knockout mice.…”
Section: Hyperglycemiamentioning
confidence: 80%
See 1 more Smart Citation
“…The beneficial effects of CCR5 deficiency were correlated with reduced recruitment and the M2dominant shift of macrophages in adipose tissues (Kitade et al, 2012). However, this finding is contrary to Chou et al' s studies, which suggested that the CCR5 gene knockout in mice impairs the regulation of energy metabolism in the hypothalamus (Chou et al, 2016). Both in vitro tissue culture and ex vivo stimulation studies indicated that the activation of PI3K-Akt pathways and insulin signaling were impaired in the hypothalamus of CCR5 knockout mice.…”
Section: Hyperglycemiamentioning
confidence: 80%
“…Similarly, Pisano et al (2017) found that weight gain in patients on antipsychotics is associated with the extent of CCL5 expression. CCL5, as a neuroendocrine element, modulates food intake and body temperature of C57BL/6 mice through unidentified receptors in the hypothalamus (Chou et al, 2016), thus affecting the body weight. In a high-fat diet-induced obese mouse model (Kitade et al, 2012), CCR5 plays a critical role in adipose tissue macrophage recruitment and polarization.…”
Section: Ccr5 and Its Ligands In Metabolic Syndrome Obesitymentioning
confidence: 99%
“…Factors elevated in response to fresh vs. spent media, potentially due to nutritional cues present in fresh media, also are important in intestinal immune function. IP10, MIP1b, and RANTES are produced by intestinal epithelia as well as immune cells and have been implicated in in ammatory, metabolic or dietrelated conditions [58][59][60][61]. The shift of IL6 and IL7 from being elevated in fresh media in epithelial-only cultures to being elevated in spent media in +DC cultures re ects the signi cance of immune cells in the mucosal model's response to bacterial factors.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, there has been increasing recognition of the substantial contribution of low-grade inflammation and immune responses driven by neoantigens generated by oxidative stress and modulated by RANTES, in causing hypertension [29]. In terms of its central activity, activation by RANTES of its receptor, the C-C chemokine receptor type 5, has been shown to stimulate insulin signaling in hypothalamic neurons, modulating systemic insulin responsiveness [30], as well as act at the level of the pancreas to promote progression to diabetes [31]. Activation of C-C chemokine receptor type 5 has further been shown to modulate social behavior in mice [32], and RANTES has been reported to increase excitatory glutamate release in the brain, promoting excitotoxic damage [33], and it may augment inflammatory brain tissue damage after stroke [34].…”
Section: Discussionmentioning
confidence: 99%